(untitled) (LACCEI, 2024)
The objective of this work is to determine the influence of the improvement proposal on the profitability of the company Agroexports Nathanael S.A.C. Therefore, the various factors and causes that affect it were studied Also, the economic impact that it causes in the company was recognized. The main causes that affect the company’s process are the lack of a calibration and maintenance plan for scales, a lack of distribution of tasks among operators, a lack of standardization of the work system, and a lack of control procedures for the supply of raw material. The engineering methodologies proposed in this research are: QFD quality house, Failure Mode and Effects Analysis (AMFE), Six Sigma process improvement. Which will allow to improve the process of operation of the company. The results of the proposed engineering methodologies are to carry out weekly training for the operators, improve the quality inspection of raw materials when entering and leaving the processing plant, as well as carrying out biweekly maintenance on the machinery. Next, the economic / financial evaluation of the proposal for improvement in maintenance management in the production process was made, resulting in the proposed improvement being viable, since Van is equal to S/.24 236.2, with an IRR of 62.31. %, recovering the total investment in 2.9 years, which is equivalent to 3 years.